Research progress on m6A demethylase FTO and its role in gynecological tumors - Wang, SiYuan; Liu, Qin (Frontiers in Oncology, 2024)
Recent advances in genomic research have increasingly focused on the fat mass- and obesity-associated (FTO) gene due to its notable correlation with obesity. Initially explored for its contribution to increased body weight, FTO was later discovered to function as an m6A demethylase. This pivotal role enhances our understanding of its broader implications across various pathologies. Epigenetic modifications, such as m6A, have been implicated in gynecological cancers, including ovarian, endometrial, and cervical malignancies. However, the precise mechanisms by which FTO influences the development of gynecological cancers remain largely unknown. This analysis underscores the growing relevance of investigations into the FTO gene in elucidating the mechanisms underlying gynecological cancers and exploring potential therapeutic avenues.